1997
DOI: 10.1002/(sici)1097-0215(19970304)70:5<518::aid-ijc5>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection by monoclonal antibodies of the Wilms' tumor (WT1) nuclear protein in patients with acute leukemia

Abstract: The WT1 gene encodes a transcriptional regulator which during embryogenesis is involved in growth control and differentiation of diverse tissues. It is also expressed in few human malignancies, including acute leukemia. We tested 3 different monoclonal antibodies (MAbs H2, H7, HC17) and the polyvalent serum WTC-19 for WT1 protein detection in mononuclear cell (MNC) preparations of 104 newly diagnosed acute leukemia patients. Using RT-PCR, these MNC preparations were also analyzed for WT1 gene expression. The W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…In fact, a similar strong cytoplasmic staining pattern has been previously described in two nephroblastomas within areas of desmin positivity using the same antibody (31). In contrast, previous immunohistochemical reports also described a weak cytoplasmic positivity with WT1 (C-terminus) antibodies in mesotheliomas (23,25), leukemias (20), and SRBCT (24) raising the possibility of an artifact of fixation (24,31,54). Some of the tumors we examined (neuroblastomas, DSRCT, lymphomas, and Wilms' tumors) had a weak cytoplasmic reactivity and nonspecific staining could not be excluded.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In fact, a similar strong cytoplasmic staining pattern has been previously described in two nephroblastomas within areas of desmin positivity using the same antibody (31). In contrast, previous immunohistochemical reports also described a weak cytoplasmic positivity with WT1 (C-terminus) antibodies in mesotheliomas (23,25), leukemias (20), and SRBCT (24) raising the possibility of an artifact of fixation (24,31,54). Some of the tumors we examined (neuroblastomas, DSRCT, lymphomas, and Wilms' tumors) had a weak cytoplasmic reactivity and nonspecific staining could not be excluded.…”
Section: Discussionsupporting
confidence: 67%
“…However, an activator or oncogenic behavior may be acquired by missense mutations. WT1 expression has been demonstrated in hema-tological malignancies (17)(18)(19)(20)(21)(22), mesothelial-derived neoplasms (23)(24)(25)(26)(27), breast cancer (28,29), genitourinary tumors (30,31), and small round blue cell tumors (SRBCT; 24,27,[32][33][34]. Recent studies have evaluated the possible role of peripheral blood RNA (18,19), serum antibodies (35), and immunotherapy (36,37) in the diagnosis, monitoring, and treatment of WT1-positive tumors.…”
mentioning
confidence: 99%
“…4 Blasts of the majority of acute myeloid and lymphoid leukemia patients express WT1, whereas patients with reactive changes to their bone marrow due to infections or malignancies show no significant WT1 expression. 5,6 WT1 expression is not detectable in patients with leukemic low-grade non-Hodgkin's lymphoma (NHL) or in patients with chronic myeloid leukemia in chronic phase. Stem cell preparations of solid cancer patients express WT1 at low levels, if at all.…”
mentioning
confidence: 99%
“…Several row samples of 125 patients with de novo acute myeloid leukeauthors [10][11][12][13][14][15][16][17] have shown that in the majority of AML cases mia at diagnosis by two-step RT-PCR. The sensitivity of the WT1 is expressed.…”
mentioning
confidence: 99%